A Fatal Case of Septic Shock Secondary to Acinetobacter Bacteremia Acquired from a Platelet Transfusion. (27th December 2019) - Nevala-Plagemann, C.; Powers, P.; Mir-Kasimov, M.; Rose, R.
Abstract : Background . Transfusion of blood products is a frequent and often necessary lifesaving intervention. While changes to blood bank practices over the past several decades have reduced the infectious complications associated with transfusions, risks still exist. Septic transfusion reactions caused by bacterial contamination of blood products, especially platelets, still occur relatively frequently. Unfortunately, clinical recognition of septic transfusion reactions is difficult due to significant symptom, exam, and laboratory abnormality overlap between different types of transfusion reactions, as well as other conditions. Novel methods have been developed to detect blood product contamination but have yet to be widely implemented in the United States. Case Report . A 67-year-old male with chronic thrombocytopenia was transfused with platelets prior to a planned procedure. Shortly afterwards, he developed fever and hypotension. He was transferred to the intensive care unit where he was treated with aggressive fluid resuscitation and broad-spectrum antibiotics. The patient went on to develop progressively worsening shock and profound disseminated intravascular coagulation. Blood cultures from the patient and the transfused platelets grew an Acinetobacter species. Despite aggressive resuscitative efforts and appropriate antibiotics, the patient died approximately 48 hours following the transfusion reaction. Conclusion . We report a fatal case of septic shock associated with Acinetobacter bacteremia caused by platelet transfusion. Our review of the literature revealed only one other documented platelet transfusion associated fatality caused by Acinetobacter species. Novel pathogen reduction and contamination detection methods have been developed but have yet to be widely adopted in the United States.